Is Minimally Invasive Surgery the Standard of Care for Ventral Hernia Repair? - Kaushik Bhattacharya (Rambam Maimonides Medical Journal)
When patients undergoing ventral or incisional hernia repair are reoperated for recurrence with an incidence rate of 16.0% following open repair and 18.8% following minimally invasive repair, it is time for re-evaluation of the real benefit of laparoscopy in ventral hernia repair.